Replication Data for: Trade-Offs and Synergies Associated With Maize Leaf Stripping Within Crop-Livestock Systems in Northern Ghana - International Food Policy Research Institute; Kizito, Fred (International Food Policy Research Institute, 2021)
The dataset contains the data and scripts required to generate the tables and figures in the article titled "Trade-offs and synergies associated with maize leaf stripping within crop-livestock systems in Northern Ghana."